Pallidotomy - outdated procedure or modern therapeutic alternative? - a review - Agnieszka Pociecha; Marta Kozikowska; Bożena Kmak (Kazimierz Wielki University, 2024)
Introduction and purpose Pallidotomy is a neurosurgical procedure involving the ablation of the globus pallidus, resulting in reduced activity in this area of the brain. Pallidotomy is an irreversible stereotactic procedure performed only under local anesthesia. It was first used in the treatment of dyskinesias associated with Huntington's chorea, but its widespread application has been in Parkinson's disease. This method is increasingly less common in developed countries due to its replacement by deep brain stimulation (DBS); however, it remains an effective treatment, particularly in drug-resistant, idiopathic Parkinson's disease. Unilateral pallidotomy is considered safer than bilateral pallidotomy due to the risk of severe complications, and thus, the bilateral approach is not recommended. Materials and methods A comprehensive literature review was conducted through an extensive bibliographic search, with a primary focus on original research articles obtained from reputable databases such as PubMed, BioMed Central, Polish Medical Platform, and Google Scholar. The search was specifically targeted towards articles pertaining to Pallidotomy. Conclusions The study shows that pallidotomy is a well-established neurosurgical treatment primarily used in drug-resistant Parkinson's disease. It should only be performed in centers specializing in stereotactic procedures. Symptoms that respond best to pallidotomy are those that previously responded to treatment, such as rigidity and tremors. The replacement of pallidotomy by deep brain stimulation (DBS) is due to the increased safety, effectiveness, and the availability of bilateral and continuous stimulation. Bilateral pallidotomy leads to severe complications and is currently not recommended. Pallidotomy has become a procedure used in specific situations and may be an alternative surgical treatment when there are contraindications to deep brain stimulation.